(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
A border is drawn to indicate a region that has a shared legal and political system. The Broderissue refers to disagreements between two countries over the imaginary border line.. Natural resourcessuch as rivers, minerals, and rich land can be a major cause of border conflicts, but so can the rapidgrowth of the population, politics, culture, religion, and a host of other factors. Nepal has beenconsidered as a sovereign country since the beginning of time, with India encircling it on all three sides,a distance of 1751 kilometres. The Lipulekh border dispute between Nepal and India is now a hot topic. Inaddition to this, there are a number of additional challenges along the Nepal-India border that need to beaddressed. As a result of their long-standing amicable relations, the Nepal-India border has long beenplagued by tensions.